PENGEMBANGAN MODUL EDUKASI SINGLE PARENT ANAK JALANAN - Kurnia Vivi Elida; Elni Yakub; Zulfan Saam (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstarct: The objectives of this research to develop a single parent for street children education module in terms of material clarity, material systematics, image support, the suitability of material delivery time, material completeness, module accuracy, module usability, and module feasibility. The research method used is Research and Development (R&D). The steps used are (1) potential and problems, (2) data collection, (3) product design, (4) design validation, (5) design revision, and (6) product manufacturing. The instruments of this research are the validation sheets to get the feasibility test results, while the validators in this study is 2 validator material guidance counseling and 2 guidance counseling practitioners. The results of the study showed that a single parent education module for street children in terms of every aspect, namely (1) Quality in the aspect of material clarity is 79.16% with the "feasible" category (2) The quality in the systematic aspect of the material is 80.83% with the "feasible" category (3) The quality of the image support aspect is 72.49% with the "feasible" category (4) The quality of the aspect of the suitability of the delivery time of the material is 79.16% with "feasible" category (5) The quality of the aspects of the completeness of the material is 79.99% with the "feasible" category (6) The quality of the aspects of the module accuracy is 81.66% with the "very feasible" category (7) The quality of the aspects of the module usability is 81.85% with the category "very feasible" (8) The quality of the aspects of the feasibility of the module is 78.33% with the "feasible" category. All aspects of the development of the education module for the single parent of street children can be said to meet the expected criteria with a percentage gain of 79.15% so that it is in the "feasible" category. Thus development of single parent education module of street children, can be said to be worthy of being tested as a single parent street child service module.Key Words: Education Module Development, Single Parent, Street Children